Mycobacterium bovis and M. caprae in Bulgaria: insight into transmission and phylogeography gained through whole-genome sequencing - Violeta Valcheva; Claudia Perea; Tanya Savova-Lalkovska; Albena Dimitrova; Lukasz Radulski; Igor Mokrousov; Krustyu Marinov; Hristo Najdenski; Magdalena Bonovska (BMC Veterinary Research, 2022)
Abstract Background This study aimed to characterize recent Mycobacterium bovis/M. caprae isolates from Bulgaria by whole-genome sequencing (WGS) to gain a first insight into their molecular diversity, transmission, and position within the global phylogeography of this important zoonotic species. Results The isolates were obtained from cattle in diverse locations of Bulgaria in 2015-2020 and were identified by microbiological and PCR assays. WGS data were used for phylogenetic analysis that also included M. bovis global dataset. Thirty-seven M. bovis/caprae isolates from Bulgaria were studied and 34 of them were SNP genotyped. The isolates were subdivided into 3 major phylogenetic groups. Type Mbovis-13 (Eu2 complex [western Europe and northern Africa]) included one isolate. Mbovis-37 type included 5 isolates outside of known clonal complexes. The Bulgarian M. caprae isolates formed a sub-group within the Mcaprae-27B cluster which also included 22 M. caprae isolates from Poland, Spain, Germany, and the Republic of Congo. The Bulgarian M. caprae isolates share their latest common ancestors with Spanish isolates. The Mbovis-37 group shares a distant common ancestor (pairwise distance 22-29 SNPs) with an isolate from Poland but was very distant (> 200 SNPs) from the rest of the tree. The Mbovis-13 group shares a common ancestor with two human isolates from Germany. Phylogeographically, both M. bovis clades had limited circulation in northeastern Bulgaria while the majority of the studied isolates (M. caprae) were from central and western provinces. A phylogenetic network-based analysis demonstrated that 11 Bulgarian isolates were separated by 1 to 6 SNPs within four clusters, mostly forming pairs of isolates. Conclusion The obtained WGS analysis positioned the Bulgarian isolates within the global phylogeography of M. bovis/M. caprae. Hypothetically, the observed phylogenetic diversity may not have resulted from livestock trade routes, but instead may reflect the deeply rooted M. bovis/M. caprae phylogeography of Europe. A high level of genetic divergence between the majority of the studied isolates suggests limited active transmission of bTB in Bulgaria during the survey period. At the same time, a possibility of the endemic presence of circulating bTB strains in the form of the latent persistent disease cannot be ruled out.